2014
DOI: 10.1016/j.brainresbull.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Duration of treatment and activation of α1-containing GABAA receptors variably affect the level of anxiety and seizure susceptibility after diazepam withdrawal in rats

Abstract: Long-term use of benzodiazepine-type drugs may lead to physical dependence, manifested by withdrawal syndrome after abrupt cessation of treatment. The aim of the present study was to investigate the influence of duration of treatment, as well as the role of α1-containing GABAA receptors, in development of physical dependence to diazepam, assessed through the level of anxiety and susceptibility to pentylenetetrazole (PTZ)-induced seizures, 24 h after withdrawal from protracted treatment in rats. Withdrawal of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A previous study found that withdrawal from 2 mg/kg of chronic diazepam treatment over 14 days did not increase anxiety-like behavior in male rats (Kovačević et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
“…A previous study found that withdrawal from 2 mg/kg of chronic diazepam treatment over 14 days did not increase anxiety-like behavior in male rats (Kovačević et al, 2014).…”
Section: Discussionmentioning
confidence: 83%
“…15 The threshold dose of pentylenetetrazole (mg/kg) required to provoke seizures was calculated from the recorded volume of infusion (ml), concentration of pentylenetetrazole (mg/ml) and body-weight (kg), using the formula: volume of pentylenetetrazole (ml) Â concentration of pentylenetetrazole (mg/ml)/body-weight (kg). In accordance with our previous data, 16 parameters of the infusion (pentylenetetrazole concentration and infusion rate) were optimized such that convulsive events appear in less than 1 min in control rats.…”
Section: Intravenous Pentylenetetrazole Infusion Testmentioning
confidence: 64%
“…18,[26][27][28] Therefore, in addition to their use to study the molecular basis of alcohol reinforcement, α1 Bz β-carboline ligands which display mixed pharmacological antagonistagonist activity in alcohol P and HAD rats may be capable of reducing alcohol intake while eliminating or greatly reducing the anxiety associated with habitual alcohol, abstinence or detoxification. 18,[28][29][30] Consequently, these types of ligands may be ideal clinical agents for the treatment of alcohol dependent individuals.…”
Section: Introductionmentioning
confidence: 99%